Analysis of leaf moisture of chinese mustard green and water spinach using single-port circular SRR microwave sensor for post-harvest in the agriculture industry - Shairi, Noor Azwan; Subramaniam, Sree Aran; Zakaria, Zahriladha; Asan, Noor Badariah; Zahari, Mohd Khairy; Alam, Syah (Wydawnictwo SIGMA-NOT, 2024)
An analysis of leaf moisture for chinese mustard green and water spinach using a microwave sensor is presented in this paper. The microwave sensor is based on a Circular Split Ring Resonator (SRR) with a single-port of the input feeder. The sensor operates at resonant frequencies in the range of 3 GHz to detect different levels of moisture content of the leaves. The Circular SRR was designed in a commercialized EM simulator and fabricated using Rogers RO4350B. The permittivity of the leaf was simulated to analyze the response of resonant frequency of the Circular SRR. Then the fabricated Circular SRR was used to measure the leaf moisture of these two vegetables based on the different resonant frequencies. Results showed that frequency changes were detected for both types of vegetable leaves when the leaf's moisture decreased gradually. With this analysis, this microwave sensor can be used for post-harvest quality control in the agriculture industry.